After the revolutionary war, which branch of the government did the states make more powerful?

After the revolutionary war, the branch of the government that states made as more powerful was: the state government.

s

Question

Asked 4/18/2019 11:22:25 AM

Updated 57 days ago|8/28/2020 8:17:50 AM

1 Answer/Comment

Rating

8

After the revolutionary war, the branch of the government that states made as more powerful was: the state government.

Added 57 days ago|8/28/2020 8:17:50 AM

This answer has been confirmed as correct and helpful.

What's the area of an equilateral triangle with sides of 10 inches and height of 7 inches?
A. 70 sq. in.
B. 20 sq. in.
C. 44 sq. in.
D. 35 sq. in.

Question

Not Answered

Updated 72 days ago|8/13/2020 1:09:43 AM

1 Answer/Comment

The area of an equilateral triangle with sides of 10 inches and height of 7 inches is 35 sq. in.

Solution:

Area =1/2 *b*h =1/2 *7*10 =35 sq. in.

Solution:

Area =1/2 *b*h =1/2 *7*10 =35 sq. in.

Added 72 days ago|8/13/2020 1:09:43 AM

This answer has been confirmed as correct and helpful.

A/an _______ triangle has all three angles measuring less than 90°.
A. acute
B. scalene
C. right
D. obtuse

An "acute" triangle has all three angles measuring less than 90°.

Question

Not Answered

Updated 124 days ago|6/22/2020 10:13:30 AM

1 Answer/Comment

An "acute" triangle has all three angles measuring less than 90°.

Added 124 days ago|6/22/2020 10:13:30 AM

This answer has been confirmed as correct and helpful.

What's the area of a square picture with 16-inch sides?
A. 32 square inches
B. 256 square inches
C. 160 square inches
D. 64 square inches

Question

Not Answered

Updated 88 days ago|7/28/2020 1:03:13 PM

1 Answer/Comment

A = a^2

A = 16^2

A = 256 square inches

A = 16^2

A = 256 square inches

Added 88 days ago|7/28/2020 1:03:13 PM

This answer has been confirmed as correct and helpful.

–12x + 6 = –15x – 3 **Weegy:** –12x + 6 = –15x – 3
x= -3
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
-12*x+6-(-15*x-3)=0
3x + 9 = 3 • (x + 3)
3 = 0
x+3 = 0
x = -3 (More)

Question|Asked by Allybak

Expert Answered

Updated 4/18/2019 12:28:27 AM

1 Answer/Comment

–12x + 6 = –15x – 3 ;

-12x + 15x = -3 - 6 ;

3x = -9 ;

x = -9/3 ;

x = -3

-12x + 15x = -3 - 6 ;

3x = -9 ;

x = -9/3 ;

x = -3

Added 4/18/2019 12:28:27 AM

This answer has been confirmed as correct and helpful.

32,511,688

questions answered

There are no comments.